Pengendalian Mutu Proses Pengemasan Ikan Tuna Skipjack (Katsuwonus Pelamis) Kaleng Metode Seven Tools - Farra Debriana Verisca; A.S.F.Q.R Mubarok; B. Kusuma; A.W. Perdana (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
Skipjack tuna (Katsuwonus pelamis) is a pelagic species that migrates long distances and inhabits all tropical and subtropical waters in the world's oceans. Proper and efficient processing is required in order to maintain the quality of the fish and obtain maximum final product results. One form of processing skipjack tuna is canned tuna. The aim of this research is to analyze the quality control of the canned skipjack tuna packaging process. The method used is data analysis using the seven tools method, data is processed using flowchart, check sheets, fishbone diagrams, scatter diagrams, Pareto diagrams, control charts and managerial implications. The results of this research were that within 11 days of canned tuna production, 3 types of product defects were found. Defects consisted of 54.63% dented cans, 25.00% lid scratches, and 20.37% can body scratches. These defects are caused by various factors such as humans, machines, methods and materials. The results obtained during 11 days of observing the production process, on the control chart there were no points that passed the Upper Control Limit (UCL) or Lower Control Limit (LCL), showed that the canned tuna production process is within control limits.